Effect of ozone treatment on physicochemical parameters and ethylene biosynthesis inhibition in Guichang Kiwifruit - CAO,Sen (2022)
Abstract To determine whether ozone can regulate fruit ripening and delay fruit aging, Kiwifruit (Actinidia deliciosa 'Guichang') was fumigated with different ozone concentrations (100 μL/L, 200 μL/L, 300 μL/L) for 3 h, stored at 1 °C and 85 ± 5% RH for three months, and then matured at 20 °C and 85% RH for 12 days. Compared with controls, the optimal concentration of ozone delayed kiwifruit ripening during cold storage by delaying the respiratory burst that precedes fruit decay. Consequently, fruit firmness, nutrient content, and enzyme activity remained stable; the expression of AdACS1 and AdACO1 as well as the activity of ACC synthetase (ACS) and ACC oxidase (ACO) was downregulated, whereby ACC and MACC were accumulated. In addition, ozone-treated fruit showed significantly reduced infection with grey mold. The effect of ozone on kiwifruit at 200 μL/L was the best suited for delaying fruit senescence, maintaining high quality during storage and fruit ripening compared with other fruits. Overall, our study indicated that ozone may play a major residual role in the physiological process of fruit ripening; furthermore, ozone can affect ethylene biosynthesis and fruit changes associated with endogenous ethylene production.